A Case of Rapidly Progressive Renal Failure with Unearthed Amyloidosis - Azad, Pulak; Jha, Lakshmi Kant; Rizvi, Yasir Sultan; Tyagi, Pranav (Journal of Clinical Nephrology, 2025)
Amyloidosis-associated kidney disease commonly manifests with chronic glomerular symptoms including heavy proteinuria predominantly albuminuria. Clinical presentation ranges from full-blown nephrotic syndrome, hematuria, and hypertension to renal failure. In India patients with chronic kidney disease are mainly attributed to hypertension and diabetes but an underlying etiology such as amyloidosis needs to be unearthed and shouldn’t be ignored as an etiology. We report a case of a 60-year-old man with hypertension and hypothyroidism who presented with frothy urine for several years, b/l pedal edema for 15 days. Over the past 3 months, there was a serial increase in creatinine. As per CKD-EPI equation, the patient was CKD-4. As the patient was suspected to be rapidly progressive renal failure; a renal biopsy was planned. Biopsy reports were suggestive of Amyloidosis. Glomerular, vascular, and tubulointerstitial deposition of amyloid was seen. Based on renal biopsy and IHC staining; the patient’s diagnosis was AA-associated secondary renal amyloidosis. Thus in this case renal amyloidosis was an unearthed etiology.